Correlation between municipal human development index and stroke mortality: a study of Brazilian capitals - Diego Monteiro de Melo Lucena; Francisco Winter dos Santos Figueiredo; Luiz Vinicius de Alcantara Sousa; Laércio da Silva Paiva; Tábata Cristina do Carmo Almeida; Sidnei José Galego; João Antônio Correa; Erika da Silva Maciel; Fernando Adami (BMC Research Notes, 2018)
Abstract Objective To analyze the correlation between municipal human development indices (MHDIs) and stroke mortality in residents of Brazilian state capitals in 2010. A secondary data analysis was conducted in 2015 using data for the MHDI and the following dimensions: income, longevity and education which were obtained from the United Nations Development Program. Additionally, we analyzed age-standardized stroke mortality data from the Department of System Information Unified Health of Brazil. Results We observed a correlation between stroke mortality and MHDIs overall (Pearson r = − 0.563; p = 0.002) and within the following dimensions: income (Spearman’s ρ = − 0.479; p = 0.011), longevity (Pearson r = − 0.510; p = 0.006) and education (Pearson r = − 0.592; p = 0.001). We identified moderate but significant negative correlations between MHDI overall and in its individual dimensions (income, longevity, and age) and stroke mortality in Brazilian capitals. Stroke is the second leading cause of death in industrialized countries and the leading cause of death in Brazil. Therefore, the discovery of factors that may influence the epidemiology of stroke is important for the construction of adequate policies considering to the socioeconomic status in these places and with an emphasis in lower socioeconomic status places.